Relationship Between Ultrasound Features and Ki-67 Labeling Index of Soft Tissue Sarcoma - Wang, Pingping; Li, Hai; Hu, Yu; Peng, Xiaojing; Ye, Xinhua; Xu, Di; Li, Ao (Frontiers in Oncology, 2021)
Objectives: To explore the relationship between ultrasound (US) features and Ki-67 labeling index (LI) of soft tissue sarcoma (STS). Methods: 46 patients with 47 STS lesions, between September 2014 and April 2020, were enrolled in the study. Point-biserial correlation analysis and Spearman's correlation analysis were utilized to examining the relationship between the US features and the Ki-67 LI of STS. The differences of US features between high and low Ki-67 proliferation groups were statistically analyzed by independent t test, Wilcoxon rank-sum test and Fisher’s exact test. The optimal cut-off points of US features revealing significant differences were estimated by the maximum Youden index. Results: A moderate correlation between the vascular density grade and the Ki-67 LI (ρ=0.409, P = 0.004) was found in this study. In addition, other ultrasound features were irrelevant to the Ki-67 LI. The cut-off for differentiating low and high proliferation groups was grade II according to the best Youden index. The area under receiver operating characteristic (ROC) curve was 0.74 (p=0.011) with a sensitivity of 60.6% and specificity of 78.6%. Conclusions: Only the vascular density grade of STS had a weak positive correlation with Ki-67 LI, and might be capable of predicting the proliferation of STS. Other ultrasonographic features of STS such as shape and tumor margin have no correlation with Ki-67 LI.